2018
DOI: 10.1182/bloodadvances.2018024018
|View full text |Cite
|
Sign up to set email alerts
|

Advanced forms of MPNs are accompanied by chromosomal abnormalities that lead to dysregulation of TP53

Abstract: The Philadelphia chromosome–negative myeloproliferative neoplasms (MPNs), including polycythemia vera (PV), essential thrombocythemia (ET), and the prefibrotic form of primary myelofibrosis (PMF), frequently progress to more overt forms of MF and a type of acute leukemia termed MPN-accelerated phase/blast phase (MPN-AP/BP). Recent evidence indicates that dysregulation of the tumor suppressor tumor protein p53 (TP53) commonly occurs in the MPNs. The proteins MDM2 and MDM4 alter the cellular levels of TP53. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 56 publications
1
52
0
Order By: Relevance
“…The most significant findings of our study involve the gain of the long arm of chromosome 1, a high-risk feature observed in ~40% of MM cases and in several other types of cancer, including breast cancer, hepatocellular carcinoma and myeloproliferative neoplasms [38][39][40][41] . Patients affected by monoclonal gammopathy of undetermined significance (MGUS), a precursor of MM, and smoldering MM (SMM) who carry gain(1q) have higher risk of progression to MM, with a median time to progression of two years 42,43 .…”
Section: Discussionmentioning
confidence: 75%
“…The most significant findings of our study involve the gain of the long arm of chromosome 1, a high-risk feature observed in ~40% of MM cases and in several other types of cancer, including breast cancer, hepatocellular carcinoma and myeloproliferative neoplasms [38][39][40][41] . Patients affected by monoclonal gammopathy of undetermined significance (MGUS), a precursor of MM, and smoldering MM (SMM) who carry gain(1q) have higher risk of progression to MM, with a median time to progression of two years 42,43 .…”
Section: Discussionmentioning
confidence: 75%
“…Studies have shown that TP53 mutations occur at a low frequency in chronic-phase MPNs and increase signi cantly according to disease progression. TP53 mutations were positively correlated with poor survival outcomes, including early death [4,5,21], and − 7/del(7q) was associated with poor survival in PMF patients [32]. Because all patients with TP53 mutations had a complex karyotype, we postulated that presence of TP53 mutation resulted from accumulation of genetic aberrations through disease progression.…”
Section: Discussionmentioning
confidence: 98%
“…Important gene mutations associated with patient outcomes, such as mutations in TP53 and ASXL1, have been identi ed using NGS approaches. [4][5][6][7][8] Risk strati cation of MPNs is based on clinical and hematologic features. Advanced age, leukocytosis, and venous thrombosis are considered risk factors for survival in PV [9] and ET [10].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, co-occurrence of gain(1q) with the t(4;14) MMSET translocation was significantly enriched in subgroup 2e and was the most significant and frequent event associated with poor outcome, as further confirmed in an independent dataset. Gain(1q) is observed in ~40% of MM cases and in several other types of cancer, including breast cancer, hepatocellular carcinoma and myeloproliferative neoplasms, and has been the subject of numerous studies in the past decade [40][41][42][43] . A recent study has shown that newly diagnosed MM patients with gain of 1q who received induction therapy with bortezomib, lenalidomide and dexamethasone (VRD) are at higher risk of early relapse, especially when amp(1q) is detected 28 .…”
Section: Discussionmentioning
confidence: 99%